Possíveis relações entre formas de provimento do cargo e percepções de diretores escolares sobre o exercício de suas funções - Silveira, Caroline Rodrigues (2016)
The globalization process experienced in recent decades has been responsible for numerous social, political and cultural factors that have changed society and, consequently, how the education has to be conceived. Such changes have brought a market bias for practices related to school management, since increased to autonomy of the institutions as regards the financial aspects. Concurrently with this, it has become the rule, from the 1988 Federal Constitution and the Law of Directives and Bases of National Education 1996, a democratic bias of school management, from which communities and families should actively participate in decisions on school environment. Since then, many were the struggles for democratic management in fact happen in schools, marking thus the search for a quality education for all. However, in some municipalities it is not a rule, since the provision mode of public school management positions still occurs from political statements, in view of external interests to the school environment and their present needs. Thus, this study aims to analyze the perceptions of four public school principals of a town in the interior in order to understand their relationship with the position of the provision so that in this case, is given by political appointment. Through interviews with such directors could realize their ideas about education, school management, indiscipline and other pedagogical aspects are closely linked to the political aspects of his office, greatly changing the way the actions are developed in practice and how education it is designed and developed.